The effect of vitamin C supplementation on maximum physical activity toward leucocytes total - Syahruddin, Syahruddin; Manfred Mandosir, Yohanis; Eka Wijaya Putra, I Putu; Sinaga, Evi; Kristanto, Budi (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2021)
The purpose of study was to determine the effect of vitamin C supplementation on maximum physical activity on the total of leukocytes. Research method used a quasi-field experiment with pre-test design and post-test control group design. The study subjects consisted of four male non-athletes, aged 20-22 years. The number of leukocytes was measured before and after vitamin C supplementation with a dose of 100 mg and 500 mg in maximum activity, namely running to fatigue. Data normality was tested by Kolmogorov Smirnov and paired sample t-test was used to test for differences in the total of leukocytes before and after vitamin C supplementation. The results showed that the average number of respondents' leukocytes increased after maximal physical activity (∆ = 6,775) and after vitamin C supplementation 100 mg (∆ = 1300) and 500 mg (∆ = 550). Paired t-test showed a significant difference (p = 0.019) between the total of leukocytes before and after maximum physical activity. There was no significant difference between the supplementation of vitamin C at a dose of 100 mg (p = 0.09) and a dose of 500 mg (p = 0.95) on the total of leukocytes before and after maximum physical activity. So, it is concluded that maximum physical activity increases the number of leukocytes. However, there was no difference in the number of leukocytes before and after maximum physical activity in the supplementation of 100 mg and 500 mg of vitamin C